Effects of Bilingualism Strategy on the Academic Performance of Primary School Pupils in English Studies in Ile Ife, Osun State, Nigeria - Okewole, Johnson Oludele (Indonesian Journal of Elementary Teachers Education, 2023)
Abstract This study determined the effects of bilingualism on the academic performance of primary school pupils in English Studies in Ile-Ife, Osun State. It also examined the interactive effects of sex and bilingualism on the academic performance of primary school pupils in English Studies in Ile-Ife, Osun State and further investigated the effects of the strategy on the attitude of the pupils in learning English Studies in the study area. The study utilized an experimental research design and the instruments used for data collection are Test of Knowledge of Reading Comprehension (TKRC) in English Studies and Pupils Attitude Questionnaire (PAQ) towards the effects of bilingualism strategy on the academic performance of primary school pupils in English Studies in Ile-Ife (PAQ). The sample comprised thirty three pupils of two randomly selected primary three classes of primary schools in Ile-Ife. Using Analysis of Covariance (ANCOVA), the results showed that students performed better when they were taught using bilingualism strategy than when they were taught using monolingual strategy with the statistical value of  Sig=0.024, F=5.811 (p<0.05). Result also showed that there is a transfer of knowledge of the Pupils' L1 to the understanding of English studies in the classroom and that irrespective of sex the pupils performed better when they were taught using bilingualism. The results also revealed that bilingualism has significant effect on the attitude of the pupils towards the learning of English reading comprehension The study concluded that bilingualism strategy is effective in improving the academic performance of primary school pupils in English reading comprehension in Ile-Ife, Osun State, Nigeria.  Keywords; bilingualism; english studies; strategy; academic performance